Rancangan Bangun Smart System Pelayanan Pencucian Kendaraan Mengunakan Mikrokontroler Berbasis Web - Fajar Alvin Tariq; Retno Devita; Hadi Syahputra (Journal of Computer Scine and Information Technology, 2023)
This tool makes it easier to service vehicle washing, with a smart vehicle washing service system, consumers' personal data is directly stored on the website. Where we no longer need to record consumer personal data in books. Where usually the personal data of consumers who have washed vehicles that are still recorded in the book are usually stored and can be lost or damaged. With this tool, personal data from washing consumers can be downloaded and it is simpler to store consumer data. This tool uses several components such as Arduino Mega as the main controller, ESP 8266 as a link between the hardware and the web, then there is a Keypad that is used to enter vehicle license plates, push buttons to select the type of vehicle, and RFID sensors to detect consumers who have become customers. members.